An Analysis Language Style Based on The Level of Formality According To Martin Joos Theory - Para pean silta; Godefridus Bali Geroda; Widi Syahtia Pane (Inquest Journal, 2023)
Background: This study discusses the style of language used in the movie Home Alone 2. The purpose of this study is to find out what style of language is applied in the movie "Home Alone 2" and want to know what type of language style is the most dominant in the movie "Home Alone 2" based on the theory of Martin Joos in Shuterland (2016). Methodology: This study used qualitative method, namely content analysis. The results showed that there are four styles in the film "home alone 2" namely formal style, consultative style, casual style, and intimate style Findings: In this thesis there are 52 data in the film to show language style. After doing this research, it can be concluded that the types of dominant styles that occur in the film are casual styles which represent 22 cases (42%), Consultative style 17 cases (33%), intimate style 8 cases (15%). formal style 5 cases (10%) and freezing is 0 cases (0%). Conclusion: The result is a casual style by becoming the dominant type of language style in the movie "home alone 2". Originality: This study analyzes the style of language used in the movie “Home Alone 2” based on the theory of Martin Joos. The purpose of this study is to find out what style of language is applied in the movie "Home Alone 2" and the dominant. This study used qualitative content analysis and the dominant style is casual